Review of cornea & contact lenses - Hellem, Amy ([País no identificado] : Advanced Medical Optics, 2007)
La revista de cornea y lentes de contactos trata sobre el diagnóstico diferencial oportuno y preciso que puede significar la diferencia entre el tratamiento exitoso y el trasplante de córnea.
INDICE - Corneal infiltrates - Puffery versus scientific integrity - Opti-Free replenish MPDS - Stand up to competition. Should you lead or follow in your marketing efforts? - CL considerations for the athlete - Disinfection that sizzles - Fitting the irregular cornea (part II) lens designs for unstable, oblate corneas - Warfarin recognize the early signs of anticoagulant toxicity - Infectious ulcer or sterile infiltrate? - To Rub or not to rub. this solution volume study identifies the most financially favorable contact lens care regimen. - SOS: ultraviolet radiation and the eye - NSAIDS and macular health. less inflammation means better quality of vision for patients at risk for GME
Review of cornea & contact lenses, se trabajó por analítica
El artículo está escrito en inglés
Incluye tabla
Incluye ilustración a colores
Incluye Preguntas de prueba
Incluye bibliografía en cada artículo
Keywords: OPTOMETRÍA -- PUBLICACIONES SERIADAS; ENFERMEDADES DE LOS OJOS -- PUBLICACIONES SERIADAS; OFTALMOLOGÍA -- PUBLICACIONES SERIADAS; SALUD VISUAL -- PUBLICACIONES SERIADAS